The lifelong nonlinear development of spatial variability of brain signals - Chengxiao Yang; Gen Li; Xiujuan Jing; Yifeng Wang; Jin H. Yan; Georg Northoff (Communications Biology)
Abstract The physiological information carried by brain signals is distinguished by their mean and variability. Research has indicated that both the variability of local signals and the spatial mean of the whole-brain signal (known as the global signal, GS) are sensitive to brain development. This raises the question of whether the spatial variability of the whole-brain signal, referred to as global variability (GV), could potentially serve as a more specific marker of brain development. We first established the reliability of GV and its topography (GVtopo) using data from the Human Connectome Project (HCP). Then, we examined the age-related patterns of GV and GVtopo in the Nathan Kline Institute Rockland Sample (NKI-RS; N = 968, ages ranging from 6 to 85 years) and validated these findings in an independent dataset from Southwest University (SALD; N = 492, ages ranging from 19 to 80 years). Our results demonstrated the robustness of GV and GVtopo, with intra-class correlation coefficients surpassing 0.61. Both GV and GVtopo exhibited distinct non-linear developmental trajectories, differring from those of GS and its topography. Furthermore, GV demonstrated substantial age-predictive capability, underscoring its potential as a valuable marker of brain development and its significance for future age-related research.